THE EFFECT OF INTEREST RATE, EXCHANGE RATE, INFLATION, AND RETURN ON ASSETS (ROA) ON STOCK PRICE IN THE BANKING SUB SECTOR LISTED ON THE IDX - Hulu, Merfiani; Pinem, Harmonika Br; Pratama, Ayang; Lubis, Yeti Meliany (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Study This own objective for know The Effect of Interest Rates, Inflation, Exchange Rates, and Return On Assets (ROA) on Stock Prices in the Banking Sub-Sector on the Indonesia Stock Exchange for the 2018-21 period. Data that used sourced from financial data on the Indonesia Stock Exchange via the website www.idx.co.id and has made selections based on criteria that have been determined. The population used in the study is Bank companies totaling 47 companies, using a purposive sample, then a sample obtained from as many as 25 companies. With study, This expected agar can become something knowledge To help researchers next, and also the students or public general need something source information. From research, can is known that the Return On Assets (ROA). Partial effect and experience significant to price stock. Interest Rates, Exchange Rates, Inflation in a manner partial No effect and not experience significant to price shares in Sub - Sectoral Banking. However, all variables have an effect simultaneously. Election sector in research This because the moment is because Indonesia already enter an era of more globalization forward, and of course, will There is Lots comer foreign or definite locals will need various type need trees, so many businesses or built companies on the basis that makes us intend To research it.